Suee and the shadow - Ly, Ginger (Amulet Books, 2017)
Twelve-year-old Suee Lee dresses all in black and has no friends--just the way she likes it. Transferring to the dim, boring Outskirts Elementary, Suee suddenly hears a strange voice speaking to her from the school's exhibit room. Then, her shadow comes to life, something dark and sinister which puts Suee and her classmates in trouble.